Harelquin fetus: a rare presentation - Quddush, ASM Rushul; Hasan, Mahmud Javed; Rowshan, Afsana; Rahman, Masudar; Rayan, Junna; Sattar, Shamima; Khan, Mahbul Ul Karim; Islam, Md Nazrul (Community Based Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/cbmj.v1i2.13866 Community Based Medical Journal Vol.1(2) 2012 59-62